Development of Punctuation theory in First Quarter of 21st Century: Main Trends - K. Ya. Seagal (Научный диалог)
A generalization of the main trends in the development of the Russian and English punctuation theory in the first quarter of the 21st century is presented, namely, relatively stable trends in the analysis of punctuation within the framework of the communicative-pragmatic approach and punctuation activity in its functional diversity. The relevance of the study lies in the following: there is still no idea of what has been done in the theory of punctuation in the first quarter of the 21st century and what are the main trends in its development. The novelty of the study is in the disclosure of how the theory of punctuation is covered through the prism of a communicative-pragmatic approach. An analysis of the development of punctuation theory in the first quarter of the 21st century is based on Russian and English publications from 2000 to 2021. It is shown how in the theory of punctuation of the first quarter of the 21st century, on the basis of a communicative-pragmatic approach, the principles and functions of punctuation, the relationship between the punctuation mark and the punctuation position, the grounds for the priority of punctuation marks, the verbalization of punctuation marks, punctuation variance, the semantic potential of punctuation, textual punctuation are considered. In addition, it is demonstrated how the functional diversity of punctuation activity, including the use of punctuation marks in computer-mediated communication is covered.